Interbrain synchronization in classroom during high-entropy music listening and meditation: a hyperscanning EEG study - Gao, Junling; Leung, Hang Kin; Lee, Kin Cheung (George); Poon, Chun Chi; Huang, Gan; Liao, Junhao; Wu, Bonnie Wai Yan; Thach, Thuan Quoc; Ho, Rainbow Tin Hung; Sik, Hin Hung (Frontiers in Neuroscience, 2025)
IntroductionSocial interaction is a vital source of human development, yet neuroscientific research delineating its neural correlates in large groups is scarce. Music as a rhythmic signal, and meditation, have been shown to induce group synchronization and pro-social behavior. However, their impact on adolescents may vary, and the related brain functions remain underexplored. This study investigates the effects of mindfulness meditation and 6 Hz high-entropy music on brain synchronization and complexity in high school students.MethodsTwenty-eight adolescents underwent single-channel EEG at the forehead during three 5-minute conditions: rest, meditation, and 6 Hz high-entropy music. Alpha band power correlations assessed synchronization. Graph analyses quantified network properties.ResultsMean correlation was highest during music, then meditation, and lowest during rest, with significant differences between music and both rest and meditation. Meditation had the highest clustering coefficient and small-world index, suggesting more integrated and efficient networks. Music demonstrated the largest information cascades and synergy, indicating extensive information integration.Conclusion6 Hz high-entropy music induced the strongest synchronization. While meditation and music altered brain dynamics compared to rest, they worked distinctly. Meditation yielded more integrated connectivity; music yielded the greatest element-wise correlation. Future research with larger samples is recommended to optimize interventions for adolescent well-being and social connectedness.